Automated Inventory Management Systems and its impact on Supply Chain Risk Management in Manufacturing firms of Pakistan - Asima Saleem (International Journal of Supply Chain Management, 2020)
Inventory management is an important task for manufacturing firms of Pakistan. Supply chain risks are considered to be major hurdle in successful accomplishment of today’s supply chain management processes. The increasing complexity in business operations results in number of supply chain risks which negatively affects the performance of an organization. This research investigates the contribution of automated inventory management systems in increasing the efficiency of inventory management. This study utilizes four automated inventory management systems which includes Radio frequency Identification (RFID), Enterprise Resource Planning (ERP), Electronic Data Interchange (EDI) and Material Requirements Planning (MRP) and analyzes their role as a supply chain risk mitigation strategy through implication of risk management process. This study also determines the moderating influence of employee training and development on the relationship between automated inventory management systems and supply chain risk management in manufacturing firms of Pakistan through the implication of Strategic Employee Training and development model. This study proves that effective employee training and development is a necessary tool for impactful diffusion of innovative inventory management systems and its implementation in supply chain risk management. Multimethod quantitative study is implied for conducting the study. Preacher and Hayes (2007) Process Model 1 on SPSS is used for moderation test.